Dynamic covalent macrocycles co-delivering genes and drugs against drug-resistant cancer - Lyu Yonglei; Wu Xiaoxia; Papageorgiou Anastassios C.; Yang Jinghui; Wang Xin; Qi Dawei; Li Jianwei (Cell Press Elsevier Inc., 2022)
Polymeric carriers have dominated the development of delivering chemotherapeutic drugs and genes against drug-resistant cancer. However, the biocompatibility, loading, and release capabilities of polymers are unsatisfactory. Here, we have advanced the delivery system by developing dynamic covalent macrocycles using a dithiol monomer through a thiol/disulfide exchange reaction to co-deliver doxorubicin (DOX) and small interfering RNA (siRNA). Our thermodynamically based macrocycles achieve a drug-loading content of 30.2%, whereas a disulfide polymer prepared from the same monomer under kinetic control cannot load DOX. In combination with siRNA, the macrocycles exhibit excellent delivery efficiency and enhanced anti-tumor efficacy in vitro without systemic toxicity. Our findings suggest that dynamic covalent chemistry offers a powerful strategy for exploring macrocyclic carriers that could replace conventional polymers for co-delivery systems, paving the way to more efficient clinic therapies.